2011
DOI: 10.1002/nvsm.415
|View full text |Cite
|
Sign up to set email alerts
|

Feeling poor, acting stingy: the effect of money perceptions on charitable giving

Abstract: In philanthropic research, much attention has been given to the impact of the actual costs of giving. In this paper we argue that, in addition to actual costs, the perceived costs of giving should be taken into consideration when seeking to understand the incidence and scale of charitable giving. We know from the economic and sociological literature that people differ in their attitudes towards money (Furnham and Argyle 1998;Zelizer 1989) attitudes towards money are rarely considered as a key explanatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 31 publications
2
57
1
7
Order By: Relevance
“…Schlegelmilch et al (1997) found that those who felt they had more discretionary income gave more to charity. This may indicate a personal variable of a "well-off feeling" that influences donation behavior and is reflected in individuals' attitudes toward money when they have higher disposable income (Wiepking & Breeze, 2011;Woodyard & Grable, 2014). It was also found that people with a higher disposable income tend to donate more to charities that are concerned with the environment, third world issues, or other global worldwide issues.…”
Section: Demographic Factorsmentioning
confidence: 95%
“…Schlegelmilch et al (1997) found that those who felt they had more discretionary income gave more to charity. This may indicate a personal variable of a "well-off feeling" that influences donation behavior and is reflected in individuals' attitudes toward money when they have higher disposable income (Wiepking & Breeze, 2011;Woodyard & Grable, 2014). It was also found that people with a higher disposable income tend to donate more to charities that are concerned with the environment, third world issues, or other global worldwide issues.…”
Section: Demographic Factorsmentioning
confidence: 95%
“…Bakija and Heim (2008) found strong evidence for parameter heterogeneity across income classes: for those with incomes below US$200,000 the persistent price elasticity was estimated at -0.699, for incomes between US$200,000 and US$500,000 this was -0.772, for incomes between US$500,000 and US$1 million this was -0.832 and for incomes over US$1 million this was -1.079. Havens et al (2007) and Wiepking and Breeze (2012) showed that not only does the relationship between absolute financial resources and giving matter for people's philanthropic behaviour, but also their perception of their financial resources. People who perceived their financial situation as more positive were more generous donors (Havens et al, 2007;Wiepking and Breeze, 2012).…”
Section: Fiscal Incentives and Givingmentioning
confidence: 99%
“…Havens et al (2007) and Wiepking and Breeze (2012) showed that not only does the relationship between absolute financial resources and giving matter for people's philanthropic behaviour, but also their perception of their financial resources. People who perceived their financial situation as more positive were more generous donors (Havens et al, 2007;Wiepking and Breeze, 2012). One study that included several background characteristics but not actual income found that those who considered themselves 'financially better off than most other people' reported higher donations to relief appeals (Bennett and Kottasz, 2000).…”
Section: Fiscal Incentives and Givingmentioning
confidence: 99%
“…Inducing a feeling of financial scarcity, such as by having participants report their savings on a scale ranging from $0 to over $50,000 as compared with a scale from $0 to over $500, also reduced charitable giving (Herzenstein and Small, 2012). Another analysis found that it was not the objective adequacy of one's wealth, but rather one's emotional feelings about the adequacy of one's wealth that most strongly predicted charitable giving (Wiepking and Breeze, 2012).…”
Section: "Manage Decision Avoidance" [Relative To Its Alternatives]mentioning
confidence: 99%